Accelerating and Innovating Climate Action : A Retrospective of the World Bank’s Experience with Select Climate and Carbon Trust Funds - World Bank (World Bank, Washington, DC, 2020)
This retrospective examines how the World Bank’s strategic use of climate-related trust funds has enabled it to play an outsized role in catalyzing climate action worldwide for nearly 30 years. By looking back at the history of climate and carbon finance, with a focus on the pioneering role of the Global Environment Facility (GEF) and World Bank carbon funds in spurring climate change mitigation activities, this report draws lessons and recommendations on how the World Bank and the wider development community can continue to benefit from climate-related trust funds to support countries in meeting their Paris Agreement commitments and achieving their sustainable development and poverty reduction goals.